Clinical and economic implications of upper gastrointestinal adverse events in Asian rheumatological patients on long-term non-steroidal anti-inflammatory drugs - Pok, Say Lee; Shabaruddin, Fatiha Hana; Dahlui, Maznah; Sockalingam, Sargunan; Mohamed Said, Mohd Shahrir; Rosman, Azmillah; Lau, Ing Soo; Isa, Liza Mohd; Hussein, Heselynn; Ng, Chin Teck; Mahadeva, Sanjiv (Wiley, 2018)
Aim: To determine the incidence and direct costs of NSAID-induced upper GI adverse events in Malaysian rheumatology patients. Methods: A retrospective, multi-centre, cohort study of rheumatology patients on long-term NSAIDs was conducted. Clinical data of patients treated between 2010 and 2013 were collected for a 24-month follow-up period. The costs of managing upper GI adverse events were based on patient level resource use data. Results: Six hundred and thirty-four patients met the inclusion criteria: mean age 53.4 years, 89.9% female, diagnosis of rheumatoid arthritis (RA; 59.3%), osteoarthritis (OA; 10.3%) and both RA and OA (30.3%). Three hundred and seventy-one (58.5%) patients were prescribed non-selective NSAIDs and 263 (41.5%) had cyclo-oxygenase-2 inhibitors. Eighty-four upper GI adverse events occurred, translating into a risk of 13.2% and an incidence rate of 66.2 per 1000 person-years. GI adverse events comprised: dyspepsia n = 78 (12.3%), peptic ulcer disease (PUD) n = 5 (0.79%) and upper GI bleeding (UGIB) n = 1 (0.16%). The total direct healthcare cost of managing adverse events was Malaysian Ringgit (MR) 37 352 (US dollars [USD] 11 419) with a mean cost of MR 446.81 ± 534.56 (USD 136.60 ± 163.42) per patient, consisting mainly of GI pharmacotherapy (33.8%), oesophagoduodenoscopies (23.1%) and outpatient clinic visits (18.2%). Mean cost per patient by GI events were: dyspepsia, MR 408.98 ± 513.29 (USD125.03 ± 156.92); PUD, MR 805.93 ± 578.80 (USD 246.39 ± 176.95); UGIB, MR 1601.94 (USD 489.74, n = 1). Conclusion: The economic burden of GI adverse events due to long-term NSAIDs use in Malaysian patients with chronic rheumatic diseases is modest.